Phonon-enhanced photothermoelectric effect in SrTiO3 ultra-broadband photodetector - Xiaowei Lu (Nature Portfolio, 2019)
Broadband photodetectors for various applications are in high demand, however, often suffering from non-linearities at high power densities. Here, a reduced strontium titanate based photodetector exhibiting linear response up to 1235 W/cm2 is presented not achieved by other broadband photodetectors.